New Drugs for Hepatic Fibrosis - Shan, Liang; Wang, Fengling; Zhai, Dandan; Meng, Xiangyun; Liu, Jianjun; Lv, Xiongwen (Frontiers in Pharmacology, 2022)
The morbidity and mortality of liver fibrosis caused by various Etiology are high all over the world, and the trend is increasing year by year. At present, there is no effective method to cure liver fibrosis except liver transplantation, and its serious complications threaten the health of patients and cause serious medical burden. In addition, there is no specific drug for the treatment of liver fibrosis, and many drugs with anti-liver fibrosis effect are in the research and development stage, so effective anti-fibrosis drugs are urgently needed. In recent years, remarkable progress has been made in the research and development of anti-liver fibrosis drugs targeting different targets. We searched websites such as PubMed, ScienceDirect and Home-ClinicalTrials.gov and found about 120 drugs with anti-fibrosis properties, some of these drugs are in phase 2 or 3 clinical trials. Ten new drugs with potential for development against liver fibrosis were selected and highlighted in this mini review. It provides reference for to provide reference for clinical drug use.